2022
DOI: 10.1155/2022/2010224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continuous and Programmed Intermittent Bolus Infusion of 0.2% Ropivacaine after Ultrasound-Guided Continuous Interscalene Brachial Plexus Block in Arthroscopic Shoulder Surgery

Abstract: Background. Despite the clinical effectiveness of the programmed intermittent bolus (PIB) method for epidural analgesia, evidence for this method in continuous interscalene brachial plexus block (CIBPB) is unclear. This study aimed to investigate the pain relief effect after arthroscopic shoulder surgery according to the administration method by comparing the PIB and continuous infusion methods among the administration methods of local anesthetics. Methods. Sixty-four patients aged >19 years scheduled for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Ropivacaine hydrochloride is the most widely used local anesthetic for nerve block in the clinic at present, and the concentration used in the clinic varies from 0.1 to 1%. [18][19][20] Because the sciatic nerve of C57BL/6 mice is thinner than the peripheral nerve of humans and direct incision injection is more intuitive than puncture injection, it is not easy to cause mechanical damage to the peripheral nerve. A previous study found that local anesthetics cause significant neurotoxic damage to developing neurons, and the concentration and exposure time of local anesthetics are important factors for nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Ropivacaine hydrochloride is the most widely used local anesthetic for nerve block in the clinic at present, and the concentration used in the clinic varies from 0.1 to 1%. [18][19][20] Because the sciatic nerve of C57BL/6 mice is thinner than the peripheral nerve of humans and direct incision injection is more intuitive than puncture injection, it is not easy to cause mechanical damage to the peripheral nerve. A previous study found that local anesthetics cause significant neurotoxic damage to developing neurons, and the concentration and exposure time of local anesthetics are important factors for nerve damage.…”
Section: Discussionmentioning
confidence: 99%